Methods for Calculating Torsional Vibrations of Shafts (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article considers the processes of free and forced torsional vibrations of a shaft with a single mass, and provides basic definitions. The differential equations of free and forced torsional vibrations of a shaft with one mass are derived and their solution is given.